Exploring the relationship between exclusion and aggression in young adults - Tan, Justina Ann Qi (Nanyang Technological University, 2023)
Previous research has established that feelings of exclusion and ostracism impact aggressive behaviour. As such, this study aims to examine the exclusion-aggression link in young adults who are more responsive to social slights as compared to older adults. 134 participants were recruited via convenience sampling and through the University’s research participation programme. 125 eligible participants took part in the lab study, engaging in the cyberball task that simulated a scenario where they were potentially excluded. Assignment to the included or excluded group was random. They then completed the Point Subtraction Aggression Paradigm (PSAP) as a behavioural measure for aggression. A questionnaire was also administered to measure demographic data and self-report aggression, which is controlled for in analyses. A one-way ANCOVA found no significant differences in aggression between the included and excluded group. The findings are discussed, and potential limitations are identified. Directions for future studies are suggested to strengthen the study design.